2019
DOI: 10.1002/jor.24197
|View full text |Cite
|
Sign up to set email alerts
|

Hind‐ and midfoot bone morphology varies with foot type and sex

Abstract: Foot type has been associated with pain, injury, and altered gait mechanics. Morphological variations in foot bones due to foot type variation may impact surgical and therapeutic treatments. The purpose of this study was to utilize principal component analysis (PCA) to determine how morphology of the hind‐ and midfoot bones differs among foot types and sex. The calcaneus, talus, navicular, and cuboid were segmented using previously obtained computed tomography (CT) scans and converted to surface models. The CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 29 publications
6
22
1
Order By: Relevance
“…We described this variability as a change in the slope of the talar neck. Our results for primary shape factors in the calcaneus were very similar to previous reports 16,27 indicating mode 1 was related to the length and height of the calcaneus, mode 2 was related to differences in the inclination of the sustentaculum tali or height and width, and mode 3 was related to differences in the talar articulating surfaces (mode 3 for Tümer et al 27 ). It is important to consider the analysis methods in SSM analysis when comparing results among studies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We described this variability as a change in the slope of the talar neck. Our results for primary shape factors in the calcaneus were very similar to previous reports 16,27 indicating mode 1 was related to the length and height of the calcaneus, mode 2 was related to differences in the inclination of the sustentaculum tali or height and width, and mode 3 was related to differences in the talar articulating surfaces (mode 3 for Tümer et al 27 ). It is important to consider the analysis methods in SSM analysis when comparing results among studies.…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to our hypothesis, the male and female tali were similar in size, whereas the calcaneus in females was overall longer but thinner than in males. A recent study by Moore et al 16 employed SSM to identify sex-dependent differences in the talus, calcaneus, cuboid, and navicular. Contrary to our results, they identified subtle differences between male and female tali, and reported no sex differences in the calcaneus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sex differences in the navicular articular surface of the talus have been reported by Ferrari et al [17], who indicated that the female navicular articular surface of the talus was more twisted in the frontal plane and more curved than that in males. In contrast, a recent geometric morphometric studies [18][19][20] has not detected sex differences in the articular surface orientation of the talus. Hence, based on these previous studies, the sex-and age-related differences in the articular morphology of the talus are still under debate.…”
Section: Introductionmentioning
confidence: 67%